Declarative Speech in Onic.Esports' Instagram Caption - Siti Ramla Kadir; Yunidar Yunidar; Juniati Juniati; Mohammad Tahir; Arum Pujining Tyas (Civiliza Publishing, Indonesia., 2026)
Language is the main communication tool used by humans to convey certain thoughts, feelings, and intentions to others. The purpose of this study is to describe the form and function of declarative speech contained in the caption of the onic Instagram account, esports in the period from January to December 2025. The definition of declarative speech in this study refers to a type of speech that is able to change status, circumstances, or social situations through speech or writing supported by institutional authorities. The methodology used is qualitative descriptive with a pragmatic approach. The type of data in this study is qualitative data in the form of language units or written speech (captions) that contain declarative elements, while the source of data is the official Instagram account onic.esports. The data collection technique is carried out through the method of listening, recording, and documenting uploads that are relevant to the organization's official statement. The results of the study showed two main forms of declarative speech, namely raising such as the announcement of new players (five data), brand ambassadors (four data), and talent (five data) and firing player farewell (five data). The function of the speech act is to establish status, provide public legitimacy, and decide a person's status in the organizational structure of the e-sports team legally.